2012
DOI: 10.9799/ksfan.2012.25.3.656
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of the Sorghum(Sorghum bicolor L. Moench) Powder following Low Temperature-Microparticulation

Abstract: Two sorghum(Sorghum bicolor L. Moench cv. Hwanggeumchal-susu and Miryang 3) samples were milled using different milling methods, and their physicochemical properties were tested. Particle size was classified into five groups such as pin mill and low temperature-microparticulation(LTM; 10,000, 20,000, 30,000, and 40,000 rpm). The water absorption index (WAI), water solubility index(WSI), and a rapid Visco analyzer(RVA) were used to examine particle size distribution and color differences. Particle size of sorgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…4B). For millet and rice, Kim et al (28) and Lee and Kim (29) reported that smaller particle sizes resulted in increased WSI values and decreased WAI values.…”
Section: Resultsmentioning
confidence: 97%
“…4B). For millet and rice, Kim et al (28) and Lee and Kim (29) reported that smaller particle sizes resulted in increased WSI values and decreased WAI values.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, freeze-drying produced cricket powder with a higher capacity for rehydration than that produced by hot air-drying. This might be attributable to smaller particle size resulting from the grinding of frozen crickets or to changes in the surface structures of hot air-dried crickets due to high temperatures (Baek et al 2017;Kim et al 2012;Kim et al 2013;Lee & Kim 2011;Onayemi & Potter 1974).…”
Section: Resultsmentioning
confidence: 99%
“…In the food industry, dried powders are usually rehydrated during food processing; thus, the ability of a powder to reabsorb moisture is an important quality during processing (Kim et al . 2012). In this study, two‐spotted cricket samples that were pulverized following freeze‐drying or hot air‐drying showed high WAI values of 3.6 g/g and 3.0 g/g, respectively (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…All color values of controls were significantly different except for the a * and b * values of the samples with sizes >50 μm (p < 0.05). Kim et al (2012) reported that in general, for powders, L * values increased as the particle size decreased, whereas the a * and b * values varied according to the sample [31]. The smaller the particle size, the higher is the scattered light, and thus the higher is the L * [32].…”
Section: Colormentioning
confidence: 98%